Values Education and Quality Teaching The Double Helix Effect - Lovat, Terence; Toomey, Ron (Springer Netherlands : Imprint: Springer, 2009)
Values Education and Quality Teaching: The Double Helix Effect reports on the results of two of the major projects in the Australian Government's Values Education Program. These results point to the fact that Values Education can no longer be seen as marginal to the main role of teaching and schooling nor as a venture merely for religious schooling. In contrast, the results show that Values Education sits at the centre of teaching and schooling wherever it occurs. The importance of Values Education is in its potential to re-focus teachers and schools on their essential purpose, namely the holistic betterment of the students in their care. The focus of Values Education coincides with the results of research into student achievement that illustrate the vital role played by relationships of care, trust and respect with teachers if students are to 'do well' both academically and more broadly. It picks up on a feature of Quality Teaching research concerned with the creation of the positive and supportive learning ambience. It is a feature that can be overlooked in the concern for technique and craft . Yet research tells us that it is this ambience, and especially the positive relationships that are part and parcel of it, that is one of the essential ingredients in student achievement. Furthermore, research tells us that student achievement is more assured when those values of care, respect and trust that underpin the learning relationship are made explicit in all aspects of teaching and schooling, including in the curriculum. In this sense, Values Education might be described as the 'other side of the coin' to Quality Teaching, as its sometimes 'missing link'or, to borrow from the research fi eld of Genetics, as co-existing with Quality Teaching in a 'double helix' relationship. It is this latter description that the authors have chosen as most appropriately describing the results of the studies on which the book reports.